Pengaruh Aplikasi Fumyco terhadap Pertumbuhan Semai Bungur (Lagerstroemia speciosa (L.) Pers.) pada Media Gambut Pedalaman.: The Effect of Fumyco Application on the Growth of Bungur Seedlings (Lagerstroemia speciosa (L.) Pers.) in Inland Peat Media. - Sampang Gaman; Patricia E. Putir; Kitso Kusin; Untung Darung; Panji Surawijaya; Adi Jaya; Yutaka Tamai (JURNAL HUTAN TROPIKA, 2026)
Abstract— Bungur (Lagerstroemia spesiosa (L) pers.) is one of the forestry crops that can be harvested both in the form of timber forest products and non-timber forest products. Seedling is an important stage in the provision of planting material/seedlings because early growth will determine subsequent growth. Considering that bungur has many benefits, this plant needs to be cultivated and developed. One of the efforts on the generative propagation of bungur plants with the application of Fumyco mycorrhizal biological buds in peat planting media, this study aims to analyze the growth of bungur saplings. This research was carried out in a residential nursery in Bukit Tunggal, Jekan Raya District, Palangka Raya City. This research was conducted from April – August 2025. The tools used are a measuring bar, thermometer, polybag, sprinkler, digital camera, and tally sheet. The materials used are peat soil and Bungur saplings (Lagerstroemia spesiosa (L) pers.). Data analysis included percentage of life, plant height (cm) and number of leaves. This study used RAL with 3 (three) Fumyco treatments: Control (P0), (P1) 5 g, and (P2) 10 g. The results showed that the percentage of survival of the seedling in the 10gr Fumyco treatment had a value of 100%, followed by the 5gr Fumyco treatment of 75%, while the control treatment was 0%. The results of the analysis of the application of Fumyco biofertilizer to the height and number of leaves of the bungur plant provided an average increase in height and the number of leaves of the seedlings was better than the control.